Tsukamurella pulmonis central venous catheter infection mimicking proteinase 3-antineutrophil cytoplasmic antibody (PR3-ANCA)-associated vasculitis. Issue 3 (3rd July 2021) - Ochi, Kiyoaki; Mukai, Tomoyuki; Ota, Shigeru; Hiraiwa, Chihiro; Ikeda, Masahiko; Ikeda, Airi; Oda, Takashi; Yamamoto, Youichiro; Ueki, Toru
Abstract: A 40-year-old Japanese woman, who underwent total thyroidectomy, had suffered from repeated episodes of fever and microscopic hematuria for 3 years, which had started 3 months after central venous port catheter insertion. On admission, she had malaise and low-grade fever, and was found to have microscopic hematuria, urinary red blood cell casts, multiple pulmonary nodules, and positivity of proteinase 3-anti-neutrophil cytoplasmic antibody (PR3-ANCA), which were suggestive to the presence of ANCA-associated small vessel vasculitis. However, her blood culture and subsequent gene analysis revealed the positivity of Tsukamurella pulmonis, and she was diagnosed with Tsukamurella pulmonis bacteremia accompanying PR3-ANCA positivity. Her condition improved after the removal of the catheter and antibiotic treatment. Tsukamurella species are categorized to the order Actinomycetales and can be misidentified as other Actinomycetales without genetic analyses. This case illustrates that chronic Tsukamurella pulmonis infection can cause ANCA production and nephritis, which mimics ANCA-associated vasculitis. Thus, it is critical to diagnose these cases correctly to avoid misdiagnosis and inappropriate treatment, such as immunosuppressive treatment.